Examining prospective mathematics teachers’ computational thinking through the lens of cognitive style - Maharani, Swasti; Ardiana, Ardiana; Andari, Tri (Lembaga Pengembangan Publikasi Ilmiah dan Buku Ajar, Universitas Muhammadiyah Surakarta, 2024)
The advancement of technology and the demands of the 21st century require prospective mathematics teachers not only to be proficient in content knowledge but also to possess adaptive computational thinking (CT) skills. This study aims to explore the CT abilities of prospective mathematics teachers based on their cognitive styles, namely field-independent (FI) and field-dependent (FD). A descriptive qualitative approach was employed, involving four prospective mathematics teachers selected through purposive sampling based on the results of the Group Embedded Figures Test (GEFT) and their initial CT abilities. Data were collected through CT problem-solving tasks, think-aloud protocols, semi-structured interviews, and direct observations, and were analyzed thematically. The findings reveal that all participants demonstrated competencies in the four dimensions of CT: decomposition, abstraction, pattern recognition, and algorithmic thinking. FI participants (S1 and S2) tended to exhibit CT with symbolic and reflective characteristics, such as symbolic-structural and reflective-tactical thinking. In contrast, FD participants (S3 and S4) displayed concrete-procedural and exploratory-conceptual CT, emphasizing numerical and contextual strategies. These differences highlight the influence of cognitive styles on the CT tendencies of prospective teachers. This study underscores the importance of developing CT training programs that are adaptive to students’ cognitive styles in order to optimize their potential in mathematical problem-solving. The practical implications support the implementation of differentiated CT instruction that accommodates individual thinking preferences within mathematics teacher education.